Label-free biosensor assay decodes the dynamics of Toll-like receptor signaling - Janine Holze; Felicitas Lauber; Sofía Soler; Evi Kostenis; Günther Weindl (Nature Communications)
Abstract The discovery of Toll-like receptors (TLRs) represented a significant breakthrough that paved the way for the study of host-pathogen interactions in innate immunity. However, there are still major gaps in understanding TLR function, especially regarding the early dynamics of downstream TLR pathways. Here, we present a label-free optical biosensor-based assay as a method for detecting TLR activation in a native and label-free environment and defining the dynamics of TLR pathway activation. This technology is sufficiently sensitive to detect TLR signaling and readily discriminates between different TLR signaling pathways. We define pharmacological modulators of cell surface and endosomal TLRs and downstream signaling molecules and uncover TLR signaling signatures, including potential biased receptor signaling. These findings highlight that optical biosensor assays complement traditional assays that use a single endpoint and have the potential to facilitate the future design of selective drugs targeting TLRs and their downstream effector cascades.